Evaluation of education as a factor in the development of the creative economy: marketing aspect - Petrenko, E.S.; Koroleva А.А. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the level of education in a creative economy. A creative economy is an economy of ideas that can be created by a creative class. It is shown that the education sector should be more focused on the formation of a creative class capable of making money on new ideas. The lack of a creative class is the main cause of the economic crisis. Creativity thrives the most in a unique social environment — in an environment that is stable enough for continuous work, but which is also characterized by diversity and breadth of thinking. The article provides a comparative analysis of the state and creative potential of education in Karaganda based on the results of a survey of young people. The authors believe that the position of this audience to the greatest extent reflects the readiness of the city to form a creative business environment as part of an innovative economy. The study is based on the use of such statistical methods as grouping, non-repetitive serial sampling. The article identifies the main problems, the main factors for the development of creative professionals. It is concluded that the creative economy will be in the event that there is a creative education. The results of the study can be used to develop a program for the development of higher education in the country.